Research progress of traditional Chinese medicine in improving hepatic fibrosis based on inhibiting pathological angiogenesis - Li, Zhen; Zhu, Junfeng; Ouyang, Hao (Frontiers in Pharmacology, 2023)
Hepatic fibrosis is the formation of scar tissue in the liver. This scar tissue replaces healthy liver tissue and can lead to liver dysfunction and failure if left untreated. It is usually caused by chronic liver disease, such as hepatitis B or C, alcohol abuse, or non-alcoholic fatty liver disease. Pathological angiogenesis plays a crucial role in the development of hepatic fibrosis by promoting the growth of new blood vessels in the liver. These new vessels increase blood flow to the damaged areas of the liver, which triggers the activation of hepatic stellate cells (HSCs). HSCs are responsible for producing excess collagen and other extracellular matrix proteins that contribute to the development of fibrosis. Pathological angiogenesis plays a crucial role in the development of hepatic fibrosis by promoting the growth of new blood vessels in the liver. These new vessels increase blood flow to the damaged areas of the liver, which triggers the activation of HSCs. HSCs are responsible for producing excess collagen and other extracellular matrix proteins that contribute to the development of fibrosis. Traditional Chinese medicine (TCM) has been found to target pathological angiogenesis, thereby providing a potential treatment option for hepatic fibrosis. Several studies have demonstrated that TCM exhibits anti-angiogenic effects by inhibiting the production of pro-angiogenic factors, such as vascular endothelial growth factor and angiopoietin-2, and by reducing the proliferation of endothelial cells. Reviewing and highlighting the unique TCM recognition of treating hepatic fibrosis by targeting pathological angiogenesis may shed light on future hepatic fibrosis research.